Identification and Characterization of Aberrant GAA Pre‐mRNA Splicing in Pompe Disease Using a Generic Approach. Issue 1 (1st December 2014) - Bergsma, Atze J.; Kroos, Marian; Hoogeveen‐Westerveld, Marianne; Halley, Dicky; van der Ploeg, Ans T.; Pijnappel, W. W.
<x xml:space="preserve">Abstract</x> Pathogenic genomic variants affecting splicing are often missed and/or poorly characterized. Here a fast and simple approach is presented for the unbiased detection and characterization of such variants. The approach has been applied to the GAA gene causing Pompe disease and resulted in the detection of numerous novel splicing events. It is adaptable for application to other human monogenic disorders. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>